THE POSSIBILITY OF USING GREEN ALGAE AS FERTILIZER IN AGRICULTURE - Tleukeyeva Assel Yerzhanovna; Alibayev Nuradin; Pankiewicz Radoslaw; Issayeva Akmaral Umurbekovna (Academic Journal of Physical and Chemical Sciences, 2021)
The article presents the results of algological studies of the Koshkar-ata river and the influence of green microalgae on the physiological development of various agricultural crops. Modern technologies for the production of agricultural products, based on the widespread use of pesticides and mineral fertilizers, made it possible to largely solve the problem of providing the population with food, and at the same time gave rise to multiple environmental, medical and environmental problems, problems of ecologically clean and biologically valuable food products, land rehabilitation, restoration their fertility, etc. Therefore, the emergence of new classes of pesticides with different mechanisms of action, high selectivity and low toxicity for warm-blooded animals is very modern. Currently, the development and application of new plant protection products that are not toxic to humans and animals is of global importance. Priority is given to research aimed at creating plant protection products based on microorganisms and their metabolites, as well as searching for plant substances with potential pesticidal activity. In this regard, the question arose of finding new safe fertilizers that could also be economically viable for production on an industrial scale. One of the current trends in this industry is the use of green microalgae. It was found that the use of a suspension of microalgae on various agricultural crops increased the yield of winter wheat by 30%, beans by 28%, mung bean by 15%. Thus, the use of a suspension of green algae in agriculture saves on the use of fertilizers, due to a one-time application of the crop to the soil. Moreover, seed treatment with a suspension of green microalgae protects against decay. The main economic effect is achieved by increasing the yield by 20-25%.